2002
DOI: 10.1007/s00280-002-0504-9
|View full text |Cite
|
Sign up to set email alerts
|

Tumour cell uptake of the metastasis inhibitor ruthenium complex NAMI-A and its in vitro effects on KB cells

Abstract: These findings suggest the interaction of NAMI-A with biological components resulting in possible consequences for the distribution of the compound itself. Furthermore, NAMI-A enters tumour cells both by passive diffusion and by active transportation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Consequently, several attempts are being taken to develop inhibitors of metastases [50]. Moreover, ruthenium complexes with antimetastasis properties have been reported [51,52]. In order to test the antimetastatic ability of R5 and R6, we tested the ability of these two complexes to inhibit invasion by breast cancer cell line MDA-MB-231 cells.…”
Section: Ruthenium Complexes Inhibit Cancer Cell Metastasismentioning
confidence: 99%
“…Consequently, several attempts are being taken to develop inhibitors of metastases [50]. Moreover, ruthenium complexes with antimetastasis properties have been reported [51,52]. In order to test the antimetastatic ability of R5 and R6, we tested the ability of these two complexes to inhibit invasion by breast cancer cell line MDA-MB-231 cells.…”
Section: Ruthenium Complexes Inhibit Cancer Cell Metastasismentioning
confidence: 99%
“…An established KB cell line, derived from a human epidermal carcinoma (European Collection of Cell Cultures number 86103004) was cultured as previously described (Frausin et al, 2002). The cell population doubling time was ca.…”
Section: Methodsmentioning
confidence: 99%
“…Both in vitro and in vivo results seem to exclude DNA as the primary target for NAMI-A, whose DNA binding is much weaker than platinum complexes [15,21,22]. On the other hand, KP1019 was proved to induce apoptosis in colorectal tumor cell lines through the mitochondrial death pathway, and DNA might be a target, although studies have shown that KP1019 and cisplatin induce different types of DNA lesions [12,23].…”
Section: Introductionmentioning
confidence: 91%